Trends in Indicators of Violence Among Adolescents in Europe and North America 1994-2022 - Molcho, Michal; Walsh, Sophie D; King, Nathan; Pickett, William; Donnelly, Peter D; Cosma, Alina; Elgar, Frank J; Ng, Kwok; Augustine, Lilly; Malinowska-Cieślik, Marta; Bjereld, Ylva; Craig, Wendy (International journal of public health, 2025)
OBJECTIVES: To describe age and gender specific time trends in adolescent violence across 19 countries over 28 years. METHODS: The paper presents analysis of eight cycles of the Health Behaviour in School-aged Children (HBSC) Study from 1994-2022, involving 789,531 children aged 11, 13, and 15. Indicators of violence included physical fighting, school bullying and cyberbullying (from 2018). Log-binomial regression models were used to test for linear temporal trends, with Generalized Estimating Equations used to account for clustering by country. RESULTS: School bullying perpetration and victimization declined over time in each age/gender group in most countries. Similar declines were reported for frequent physical fighting among boys (all ages) and girls (age 15 only). The prevalence of violent behaviour was almost universally higher in boys in the early cycles than in girls, but this gender difference attenuated over time. For cyberbullying, significant increases were observed since 2018 in all groups except age 15 girls in most countries. CONCLUSION: This analysis of a large cross-national dataset suggests a decline in traditional forms of adolescent violence. However, the increases in cyberbullying warrant further monitoring.
Keywords: Adolescent Behavior; oběti zločinu; Male; Adolescent; sexuální faktory; Child; Europe; dítě; prevalence; násilí; kyberšikana; mužské pohlaví; Violence; mladiství; Evropa; lidé; ženské pohlaví; Humans; Crime Victims; Sex Factors; Prevalence; North America; Bullying; Female; Cyberbullying; šikana; chování mladistvých; Severní Amerika